Responses of thyroid activity to feed restriction in the goat. - Abdullah, Rasedee; I.R., Falconer (CSIRO, 1977)
A study of the effect of restriction of feed intake on the deiodination, faecal excretion, -distribution and secretion of thyroid hormones was carried out in a group of-eight young inale goats. ' In the control goats fed ad libitum no changes in the concentration of circulating thyroxine were observed with increasing age -or body weight during the experimental period; however, an increase in thyroxine secretion rate per animal was apparent with increasing age or body weight of'the goats. In feed-restricted goats, no changes in the peripheral deiodination of [125I]thyroxine were observed, 'though significantly reduced faecal excretion of [125I]thyroxine was seen in goats' restricted to 50 or 20% of their ad libitum feed intake. Both thyroxine turnover rate and thyroxine distribution vollime were reduced by feed restriction. The secretion'rate of thyroxine was reduced to 45 % of the rate in ad libitum fed animals when feed intake was restricted to 20 %. Calculation 'of thyroxine secretion rate per kilogramo.75 body weight showed a highly significant correlation with feed intake. It was concluded that the marked reduction in thyroid activity occurring when feed restriction was imposed would be expected to cause a physiologically significant reduction in metaholic activity.